1981
DOI: 10.1111/j.1348-0421.1981.tb00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxide Formation and Membrane Damage in Endotoxin‐Poisoned Mice

Abstract: Lipid peroxide formation and plasma membrane damage in mouse liver following the administration of Salmonella endotoxin were examined. The liver lipoperoxide level was markedly elevated in animals given endotoxin compared with that in the controls, and returned to its normal range after 2 days. On the other hand, superoxide dismutase activity was decreased by 18-48 hr after endotoxin injection, thereafter tending to increase. Glutathione reductase and glutathione peroxidase activities declined in the liver 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
32
0
1

Year Published

1984
1984
2005
2005

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 45 publications
4
32
0
1
Order By: Relevance
“…Conjugated dienes, such as malondialdehyde and 4-hydroxy-2(E)-nonenal, are recognized markers of lipid peroxidation and tissue damage. 8,[27][28][29][30] In this study, all M haemolytica-inoculated calves had significantly greater CD concentrations in lung tissue 2 and 6 hours after inoculation, compared with salineinoculated calves. This result is in agreement with results of another study in which increased lipid peroxidation was detected after pulmonary administration of endotoxin.…”
Section: Discussionmentioning
confidence: 82%
“…Conjugated dienes, such as malondialdehyde and 4-hydroxy-2(E)-nonenal, are recognized markers of lipid peroxidation and tissue damage. 8,[27][28][29][30] In this study, all M haemolytica-inoculated calves had significantly greater CD concentrations in lung tissue 2 and 6 hours after inoculation, compared with salineinoculated calves. This result is in agreement with results of another study in which increased lipid peroxidation was detected after pulmonary administration of endotoxin.…”
Section: Discussionmentioning
confidence: 82%
“…We reported previously, glutathione (GSH) reductase, and peroxidase activities and sulfhydryl level declined markedly in mouse liver by 18hr after endotoxin administration (14). Therefore, with endotoxin administration the disturbed metabolism of lipid peroxide by intramitochondrial GSH peroxidase may result in consumption of reduced GSH and in an increase in the NAD(P)+/NAD(P)H ratio (2).…”
mentioning
confidence: 99%
“…Free radical injury occurs via lipid peroxidation in a variety of disease processes including shock. We reported previously 25,26) that endotoxin injection resulted in liver lipid peroxide formation and membrane damage in experimental animals, causing decreased levels of free radical scavengers or quenchers. In a previous study, 5) we also observed that Sho-saiko-to appears to protect the liver cell plasma membrane from injury by free radicals, which occurs in the state of tissue ischemia during endotoxemia.…”
Section: Discussionmentioning
confidence: 99%